Appendiceal mucinous adenocarcinoma presenting as an enterocutaneous fistula in an incisional hernia. (12th October 2010) - Sayles, Mark; Courtney, Edward; Younis, Firas; O'Donovan, Maria; Ibrahim, Ashraf; Fearnhead, Nicola S
Abstract : A 68-year-old woman with a history of bone-graft harvesting from the right iliac crest presented with an incisional hernia and abscess at the graft donor site. Following incision and drainage of the abscess, CT demonstrated an enterocutaneous fistula between the appendix and bone-graft incision with appendicitis assumed to be the original cause of the abscess. At laparoscopy, the appendix was adherent to the hernia sac with mucinous material at the superficial orifice of the fistula site but not in the peritoneal cavity. Laparoscopic appendicectomy with fistula track excision was performed. Histological evaluation confirmed a well-to-moderately differentiated mucinous adenocarcinoma arising on a background of dysplastic villous adenoma. Tumour extended along the fistula track to involve the surface skin. A laparoscopic right hemicolectomy, lymph node dissection and wide local excision of the fistula track were carried out at a second procedure. Final histology confirmed pT4N1 tumour with clear resection margins.